The Use of Isotope Indicators in Hydrological Studies in the Taldura River Basin, Central Altai - D. V. Bantcev; A. A. Ovsepyan; V. A. Rasputina; A. V. Kozachek; K. B. Tchikhatchev; D. A. Ganyushkin (Лëд и снег)
Stable isotopes investigation was carried out in the territory of the Yuzhno-Chuya Ridge (Central Altai) during the ablation season of 2022. Samples were taken to determine the contribution of meltwater and precipitation to feeding of water bodies. The main research objects are Nekrasov glacier – Tamozennoye Lake system and Taldura River. In the basin of Lake Tamozennoye, the average ice δ18O of the Nekrasov glacier (‒17.3%) was obtained. Based on the isotopic composition of ice and precipitation, it was estimated that in the stream flowing into Lake Customs, the contribution of glacier meltwater varies from 28 to 67%, on average 54%. For a stream flowing out of a lake, the proportion of meltwater is higher: 48–72, 61% on average. First of all, meltwater enters the lake by filtration through the moraine, and not by surface runoff. Along the Taldura River, δ18O does not change significantly (δ18O –16.58 … –16.84%) for 38 km before the Taldura River confluence into the Chagan River. This indicates the complete predominance of glacier meltwater in the river feeding in the middle of the ablation season. Repeated sampling of water from the Taldura River 5 km from the edge of the glacier showed, that the effect of precipitation can be traced in the isotopic composition of river water, but it does not exceed 20%.